Analisis Yuridis Peranan Kejaksaan Dalam Sistem Peradilan Pidana di Indonesia - Mohd. Yusuf Daeng M.; Reni Astuti; Robin Eduar; Zulkardi Zulkardi; Geofani Milthree Saragih; Muhammad Fadli i’lmi (Departement of Mathematics Education, 2023)
The Attorney General's Office of the Republic of Indonesia is a government institution that has an important role in the criminal justice process which has the main task of carrying out prosecutions and other authorities that it has as one of the law enforcers. In this research, the focus that will be the main topic is the role of prosecutors in the criminal justice system in Indonesia. Prosecutors are civil servants with functional positions who have specificity and carry out their duties, functions and authorities based on the law. When he enters the trial, the Prosecutor switches status to become a Public Prosecutor (as long as he has been given a task order as a Public Prosecutor in a case). The Public Prosecutor is a Prosecutor who has been given the authority to prosecute and carry out decisions up to the Judge's decision and other matters that have been regulated in the law. This study uses a juridical normative research type by linking the subject matter to the main topic in this research, namely the role of the prosecutor in law enforcement in the criminal justice system in Indonesia.